The effect of zinc-biofortified rice on zinc status of Bangladeshi pre-school children: A randomized, double-masked, household-based controlled trial - Jongstra, Roelinda; Mokbul Hossain, Md; Galetti, Valeria; Hall, Andrew G.; Holt, Roberta R. (Elsevier, 2022)
Background: Zinc biofortification of rice could sustainably improve zinc status in countries where zinc deficiency is common and rice is a staple, but its efficacy has not been tested. Fatty acid desaturases (FADS) are putative new zinc status biomarkers. Objective: Our objective was to test the efficacy of zinc-biofortified rice in preschool-aged children with zinc-deficiency. Our hypothesis was that consumption of zinc-biofortified rice would increase plasma zinc concentration (PZC). Design: We conducted a 9-month, double-masked, intervention trial in 12–36 month-old rural Bangladeshi children, most of whem were who were zinc-deficient (PZC < 70 µg/dL) and stunted (n = 520). The children were randomized to receive either control rice (CR) or zinc-biofortified rice (BFR) provided in cooked portions to their households daily, with compliance monitoring. The primary outcome was PZC. Secondary outcomes were zinc deficiency, linear growth, infection-related morbidity, FADS activity indices, intestinal fatty acid binding protein (I-FABP) and fecal calprotectin. We applied sparse serial sampling for midpoint measures and analyzed data by intention-to-treat using mixed-effects models. The trial was registered under NCT03079583. Results: At baseline, median (IQR) PZC was 60.4 (56.3–64.3) µg/dL, 78.1% of children were zinc deficient and 59.7% were stunted. Mean ± SD daily zinc intakes from the CR and BFR during the trial were 1.20 ± 0.34 and 2.22 ± 0.47 mg/day, respectively (P < 0.001). There were no significant time-by-treatment effects on PZC, zinc deficiency prevalence, FADS activity, I-FABP or fecal calprotectin (all P > 0.05). There was a time-treatment interaction for height-for-age z scores (P < 0.001) favoring the BFR group. The morbidity longitudinal prevalence ratio (LPR) (95% CI) was 1.08 (1.05,1.12) comparing the BFR and CR groups, due to more upper respiratory tract illness in the BFR group. Conclusions: Consumption of zinc-biofortified rice for 9 months providing ∼1 mg of additional zinc daily to Bangladeshi children did not significantly affect PZC, prevalence of zinc deficiency or FADS activity. Clinical Trial Registry: https://clinicaltrials.gov/ct2/show/NCT03079583